2020
DOI: 10.3390/bs10010034
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Individual Psychological Features to the Determination of the Phenomenon of Work Alienation

Abstract: Using the questionnaire method on a sample of 92 Russian-speaking employees of the “person-person” professions type, the relationship of work alienation with personal characteristics was investigated. It was found that work alienation has associations with some personality traits. Also, the satisfaction of basic psychological needs at work is a significant predictor of work alienation. The study proved that work alienation is a relatively flexible construct for changes in the workplace that relate to autonomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Since anxiety reflects the general mood of the individual, high anxiety increases alienation from work. A supporting study concludes that depression and emotional variability are positively associated with work alienation [95]. A teacher who is in a constant state of anxiety may be less sensitive to his/her environment and problems and may experience communication problems with students and other teachers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since anxiety reflects the general mood of the individual, high anxiety increases alienation from work. A supporting study concludes that depression and emotional variability are positively associated with work alienation [95]. A teacher who is in a constant state of anxiety may be less sensitive to his/her environment and problems and may experience communication problems with students and other teachers.…”
Section: Discussionmentioning
confidence: 95%
“…When looking at the individual consequences of work alienation, negative consequences such as depression, addiction, and irregular lifestyle can be seen [37]. In addition, alienation from work negatively affects the health of employees, causing low morale and possibly leading to some psychological diseases [94,95]. These results are related to the general mood of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by [ 31 ] to investigate the work alienation among 62 university professors, they found that work alienation increased during pandemic when measured over three time points, this highlights the negative effects of work alienation in different professions. Nurses during COVID-19 often work extra time, feel separated from their families, and lack financial rewards, which can lead to accelerated work alienation among them.…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted in the past have found a significant relationship between isolation and work alienation (Forsyth and Hoy, 1978;Korman et al, 1981;Miller, 1967Miller, , 1975Nair and Vohra, 2010;Schlichte et al, 2005;Zielinski and Hoy, 1983) resulting from the psychological segregation of the worker from his/her work. Such a relationship is characterized by a subjectively experienced state linked with destruction of interpersonal relationships, which manifests itself in the form of helplessness, meaninglessness and self-alienation of the worker (Vinokurov and Kozhina, 2020). We therefore proposed that: H1.…”
Section: Work From Home-isolationmentioning
confidence: 99%